Comparing Efficacy of Standard Vs Modified Valsalva Maneuver in Terminating Paroxysmal Supraventricular Tachycardia - Rafia Shoukat, Saman Ahmad, Hafiz Muhammad Sajid Jehangir, Waqas Arshad, Zahid Hussain Shah, Tanveer Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To know whether valsalva maneuver is more effective compared to modified valsalva in terminating paroxysmal supraventricular tachycardia or vice versa. Method: The study design was randomized controlled trial. This research was conducted in accident & emergency department of Mayo hospital, Lahore. Duration of this study was nine months. Participants were divided in two groups, half were assigned in Standard VM group (Group A), and other half in Modified VM group (Group B). In both groups, assigned valsalva maneuver was repeated up to two times, only when paroxysmal supraventricular tachycardia did not revert to sinus rhythm on first time. In those patients, VM failed even after three attempts, antiarrhythmic medications were used. Primary outcome was defined on the basis of successful return of sinus rhythm after either by standard or modified valsalva maneuver. Results: Sixty two patients were included in this study, thirty one in each group. Out of thirty one patients in group A, two patients (3.2%) rhythm reverted to sinus, while in group B, seven patients (11.3%) rhythm reverted to sinus. The number of patients who needed rescue treatment was lower in group B -21 (77.4%) as compared to group A- 29(93.5%). Conclusion: The results of this study showed that modified VM was more effective in terminating PSVT as compared to standard VM. So, number of patients who required pharmacological cardioversion was lower in group B. Keywords: Supraventricular tachycardia (SVT), Standard valsalva maneuver (SVM), Modified valsalva maneuver (MVM)